L' esperienza Educativa Di San Giovanni Bosco E Santa Maria Domenica Mazzarello: Rilettura Alla Luce Della «Cultura Dell'incontro» Di Papa Francesco - Ruffinatto, Piera (Rivista di scienze dell'educazione, 2018)
The article creates a dialog between Pope Francis' perspective, which sees encounter as a reality of anthropological and theological depth, and the spiritual educational experience of Saint John Bosco and Saint Mary D. Mazzarello. The points that emerge not only show how the two perspectives enrich each other reciprocally, but also open the way for further reflection on the pedagogical meaning of encounter as a privileged place for education as well as an efficacious living of the Salesian Preventive system of education. (English)